O uso de próteses auditivas por idosos: os repertórios interpretativos utilizados nessa decisão - Ribeiro, Luciana Muniz (2008)
The aim of this study was to describe the interpretative repertoires used by hearing impaired elders, in interviews, about the decision to use or not to use hearing aids. Ten elderly individuals, five men and five women, who had acquired sensorineural hearing loss, with characteristically high frequency audiometric configuration. Five interviewees had been using hearing aids for at least five months before the interview and five sought hearing aid adaptation services, took tests, but decided not to acquire them. Data analysis was performed according to the proposals of Discourse Analysis influenced by the social constructionism approach, which includes the transcription of all of the interviews followed by their readings, making the identification of interpretive repertoires possible. We observed that the hearing aid users justified their decision through the use of five basic repertoires, which were denominated as: (1) The bothersome of repetition, (2) In search of prevention and self-care, (3) The hearing aid as a beneficial technological resource, (4) The recognition of the hearing aid limitations and (5) The virtue of resignation. On the other hand, those who decided not to use the hearing aids justified their decision using the following repertoires: (1) The use of alternative strategies, (2) The discomfort greater than the benefits, (3) The unsuccess of others, (4) The relativity of necessity and (5) The transitoriness of decision. Repertoire analysis permitted us to identify some functions of its use, as well as moral implications during this use. Therefore we could perceive that when such repertoires were used, the interviewees sought to legitimize their decision to use or not to use hearing aids, demonstrating that this decision was taken in a criterious manner, while taking into account diverse aspects, and so must be respected. Besides this, when using these repertoires, the interviewees searched reaching positive moral images, putting themselves in positions of coherent, flexible, logical, capable, responsible and informed people. In the same manner, they also try to guarantee the distancing of negative images, as difficult, inflexible and uniformed people. Besides identifying interpretive repertoires, this study made it possible for us to visualize these repertoires as mobile, or, socially available, capable of being used in a combined manner by different social groups depending on the conversational intention at the moment. In this sense, this study aimed to highlight the importance of the audiologist to be sensitive to socially available interpretive repertoires which construct, broadening or limiting possibilities regarding the decision to use or not to use hearing aids. The possibilities influence the relations that we establish with our patients, delimiting our actions of taking the patient in, dialogue and negotiation.